A Targeted Complement Inhibitor CRIg/FH Protects Against Experimental Autoimmune Myasthenia Gravis in Rats via Immune Modulation - Song, Jie; Zhao, Rui; Yan, Chong; Luo, Sushan; Xi, Jianying; Ding, Peipei; Li, Ling; Hu, Weiguo; Zhao, Chongbo (Frontiers in Immunology, 2022)
Antibody-induced complement activation may cause injury of the neuromuscular junction (NMJ), thus being considered a primary pathogenic factor in human myasthenia gravis (MG) and animal models of experimental autoimmune myasthenia gravis (EAMG). In this study, we tested whether CRIg/FH, a targeted complement inhibitor, could attenuate NMJ injury in rat MG models. We first demonstrated that CRIg/FH could inhibit complement-dependent cytotoxicity on human rhabdomyosarcoma TE671 cells induced by MG patient-derived IgG in vitro. Further, we investigated the therapeutic effect of CRIg/FH in a passive and an active EAMG rodent model. In the both models, administration of CRIg/FH could significantly reduce the complement-mediated end-plate damage and suppress the development of EAMG. In the active EAMG model, we also found that CRIg/FH treatment remarkably reduced the serum concentration of autoantibodies, and of the cytokines including IFN-γ, IL-2, IL-6 and IL-17, and up-regulated the percentage of Treg cells in the spleen, which was further verified in vitro. Therefore, our findings indicate that CRIg/FH may hold the potential for the treatment of MG via immune modulation.